Integrated management of multiple water sources for multiple uses: rural communities in Limpopo Province, South Africa - van Koppen, Barbara; Hofstetter, Moritz; Nesamvuni, A. E.; Chiluwe, Q. (Academy of Science of South Africa, 2020)
This study fills a knowledge gap about low-income rural communities’ holistic management of multiple water resources to meet their multiple needs through multiple or single-use infrastructure. Six low-income rural villages in Limpopo Province were selected with a diversity in: service levels, surface and groundwater resources, public infrastructure (designed for either domestic uses or irrigation but multiple use in reality) and self-supply (people’s individual or communal investments in infrastructure). Focusing on water-dependent livelihoods and water provision to homesteads, distant fields and other sites of use, three policy-relevant patterns were identified. First, most households have two or more sources of water to their homesteads as a vital buffer to irregular supplies and droughts. Second, infrastructure to homesteads is normally for domestic uses, livestock and, for many households, irrigation for consumption and sale. Public infrastructure to irrigate distant fields is multiple use. Exceptionally, self-supply point sources to distant fields are single use. Water bodies to other sites of use are normally multiple use. As for large-scale infrastructure, multiple-use infrastructure is cost-effective and water-efficient. Third, in four of the six villages people’s self-supply is a more important water source to homesteads than public infrastructure. In all villages, water provided through self-supply is shared. Self-supply improves access to water faster, more cost-effectively and more sustainably than public services do. In line with international debates, self-supply is there to stay and can be supported as a cost-effective and sustainable complementary mode of service delivery. A last potential policy implication regards community-driven planning, design and construction of water infrastructure according to people’s priorities. This may sustainably harness the above-mentioned advantages and, moreover, communities’ ability to manage complex multiple sources, uses and multiple-use infrastructure, whether public or self-supply, as a matter of daily life.